Investing into microfinance investment funds - Karel Janda; Barbora Svárovská (Charles University in Prague, Institute of Economic Studies (IES), 2009)
This paper investigates investment performance of microfinance investment funds. The examined funds have recorded lower total risk than global stocks and bonds (measured by four benchmark indices) with moderate but stable returns. The analysis revealed that investment in microfinance investment funds that focus especially on debt instruments represents an attractive opportunity for the portfolio diversification as this asset class does not show any positive correlation with global or emerging capital markets. At the same time, it provides adequate risk-adjusted returns and may be therefore attractive not only for investors with a particular interest in the socially responsible aspect of investment into microfinance.
Keywords: G11; G21; 330; microfinance; Investment; Funds; Mikrofinanzierung; Investmentfonds; Investition; Portfolio-Management